Development of Muslim-Friendly Service Standardization In The Halal Tourism Industry in Indonesia - Mohammad Dliyaul Muflihin; Ade Irma Suryani Lating; Nufaisa; Mochammad Ilyas Junjunan (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
The demand for halal tourism in Indonesia and even the world is very large; the government must utilise the potential to attract public interest in halal tourism. To explore the great potential of halal tourism, it must begin to provide products, facilities, and infrastructure to meet the needs of Muslim tourists with Muslim-friendly services. The aim of this research is to compile the development of standardisation services in halal tourism through halal tourism practice in Indonesia. The object of this study is the need for standardisation of Muslim-friendly services in terms of access, service, and provision of tourist facilities. This research is qualitative research using a descriptive approach. The study of literature (library research) by collecting journals that follow the research topic and analysing using data grouping, data reduction, data presentation, and conclusion. The results of this research state that many standardisation Muslim-friendly services. The standards must exist in halal tourism; in addition, these services or facilities, if possible, must be MUI certified so that tourists feel calm in using or using halal products. Â